Accuracy of heart rate watches: Implications for weight management - Wallen, M. P.; Gomersall, S. R.; Keating, S. E.; Wisløff, U.; Coombes, J. S. (PLOS ONE, 2016)
Wrist-worn monitors claim to provide accurate measures of heart rate and energy expenditure. People wishing to lose weight use these devices to monitor energy balance, however the accuracy of these devices to measure such parameters has not been established.